Efektifitas Backwashing Untuk Menjaga Kinerja Rapid Sand Filter Di Daerah Gambut - Hugo Pratama; Yohanna Lilis Handayani; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water is water that available on surface or ground water, it has been affected by the characteristic of the peat. These conditions make well water in that area can not be consumed. Water treatment process needs to be done to improve the water quality. One of them with a simple concept and experiencing is rapid sand filter. The purpose of this study was to determine the effectiveness retrospective on the addition of saturated filter backwashing installation. Reactor rapid sand filters without backwashing and rapid sand filter by backwashing made of PVC pipe diameter 6 " and high 50 cm. The results showed rapid sand filters without backwashing produce the best effectiveness to raise the pH value of 7,96 % and lowers the organic content of 29,31 %. While the rapid sand filter by backwashing produce the best effectiveness in raising the pH value of 5,81 % and lowers the organic content of 30,43 %. In general, the processed peat water from rapid sand filter is capable of improving the water quality of the peat.Keywords : peat water, rapid sand filter, backwashing, water quality